The effect of emotional ventilation on the psychosocial development of school age children during the Covid-19 Pandemic - Mariyam Mariyam; Eni Hidayati; Titik Suerni (Media Keperawatan Indonesia, 2021)
The World Health Organization has officially declared the coronavirus as a pandemic The impact of the pandemic is also experienced by children. Children experience major changes in their lives, one of which is child psychosocial. Psychosocial support needs for the children. This study aims to determine the effect of emotional ventilation on the psychosocial development of school-age children during the Covid-19 pandemic. This research design is a quasi-experiment with a one-group pretest and posttest design approach. Respondents were 43 school-age children. Psychosocial development was assessed using the Strengths and Difficulties Questionnaire (SDQ). Emotional ventilation is done once a week and twice a week. a week after the second intervention, a post-test was performed. The results showed that before the intervention prosocial behaviour, emotional problems and hyperactivity were mostly normal, behavioural problems and relationship problems with peers before the intervention showed mostly abnormal. After prosocial behaviour intervention, emotional problems, behavioural problems and hyperactivity were mostly normal and only peer relationship problems were still mostly abnormal. There are differences between emotional problems, behavioural problems, hyperactivity before and after emotional ventilation with a p-value ≤ 0.05.